Obstetric violence: an expression of the social question in the work of social workers - Corrêa, Ana Paula Dias; Torres, Iraildes Caldas (Argumentum, 2021)
The occurrence of obstetric violence has its basis in patriarchy. In capitalist society, it is mediated by inequalities of gender, class, and race/ethnicity, and manifests itself as just one expression of the social question. This article presents the results, determinants, and characteristics of obstetric violence and highlights the role of Social Work in dealing with this form of violence. The research methodology followed the guidelines for qualitative approaches in dealing with the data under analysis, from a historical-critical perspective. Among the multiple aspects identified, the high incidence of obstetric violence in a maternity hospital located in Manaus, Amazonas, is clear, a fact that presents itself within the work of the Social Worker in a more impactful way in contemporary times.